An Omnidirectional Polarization Detector Based on a Metamaterial Absorber - Binzhen Zhang; Yong Zhang; Junping Duan; Wendong Zhang; Wanjun Wang (Sensors, 2016)
The theory, design, simulation, fabrication, and performance of an omnidirectional polarization detector (PD) with two resonances located in the X and Ka ranges based on a metamaterial absorber (MMA) are presented in this paper. The sandwich structure of PD is composed of 0.1 μm periodic “I” shaped patches on the metasurface, a dielectric of 200 μm FR-4 on the interlayer, and a 0.3 μm copper film on the substrate. PD absorptivity is first used to reflect and describe the polarization of the incident wave. The numerical results, derived from the standard full wave finite integration technology (FIT) of CST 2015, indicates that the designed PD shows polarization sensitivity at all incidence angles. The effects on absorptivity produced by the incidence angles, polarization angles, and materials are investigated. The amplitude of absorptivity change caused by polarization reaches 99.802%. A laser ablation process is adopted to prepare the designed PD on a FR-4 board coated with copper on the double plane with a thickness that was 1/93 and 1/48 of wavelength at a resonance frequency of 16.055 GHz and 30.9 GHz, respectively. The sample test results verify the designed PD excellent detectability on the polarization of the incident waves. The proposed PD, which greatly enriches the applications of metamaterials in bolometers, thermal images, stealth materials, microstructure measurements, and electromagnetic devices, is easy to mass produce and market because of its strong detectability, ultrathin thickness, effective cost, and convenient process.